First Development, Optimization, and Stability Control of a Pediatric Oral Atenolol Formulation - Morri, Mauro Gaspar (2018)
Liquid formulations can be used in children of different ages by varying the volume of the administered dose in order to ensure an exact dosage. The aim of this work was to develop and to optimize a safe liquid atenolol formulation and to carry out the corresponding chemical and microbiological stability studies. A Plackett-Burman design was used to determine the factors that could be critical in the development of the formulations, and a central composite design was used to determine the optimal working conditions. As a result of these analyses, three formulations were selected and their stability studied in three storage conditions, 4, 25, and 40°C. After 6 months of stability testing, the optimal systems showed no pH change or atenolol loss; however, only glycerin-based formulations showed no microbial development. These systems, employing excipients in a range that the EMA has recommended, showed chemical and microbiological stability for at least 6 months even at the worst storage conditions.